Sextus on Ataraxia Revisited - Machuca, Diego Emanuel (2020)
My purpose is to revisit an issue concerning the state of undisturbedness or tranquility (ἀταραξία) in ancient Pyrrhonism as this stance is depicted in Sextus Empiricus’s extant works. The issue in question is whether the pursuit and the attainment of undisturbedness in matters of opinion should be regarded as defining features of Pyrrhonism, not merely from a systematic standpoint that examines Pyrrhonism as a kind of philosophy, but mainly according to Sextus’s own account of that skeptical stance. In exploring this issue, I will develop an interpretation defended in previous work, responding to some objections, discussing alternative interpretations, offering further textual support, and putting forward new arguments. It is my contention that examining whether the pursuit and the attainment of undisturbedness in matters of opinion are essential to Pyrrhonism makes it possible to gain a more accurate understanding of this brand of skepticism